The determination of the relationship between levels of narcissim and motivational trends in the individual sports branches - Tazegül, Ü. (Journal of Human Sport & Exercise, 2013)
The purpose of this study is to determine the relationship between levels of narcissim and motivational trends in the individual sports branches. The sample of the study includes a total of 350 young athletes in the branches of boxing, freestyle wrestling, Greco-Roman wrestling, taekwondo and weightlifting, participated in Turkey Youth Champions in 2011. Sport-specific motive scales (SSMS) and Narcissistic Personality Inventory (NPI) was utilized in order collect the datas in this study. SPSS 15 package software was used for the data analysis. The test of Kolmogorov-Smirnov to determine whether the data had a normal distribution , the test of Levene was applied to determine the homogeneity of variances and it was determined that the datas had an homogeneous and normal distribution. Descriptive statistics and Pearson correlation analysis were used in the analysis of the data. In the result of data analysis, there was a a statistically significant relationship between the motive to achieve success with exploitation dimension and the power motive with superior dimension. (p<0,05).